Triage in Emergency Management in the Emergency Department: A Systematic Review - Richal Grace Zefanya Uly; Sriyono Sriyono; Arina Qona'ah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Triage is a vital process aimed at categorizing patients based on the severity of their conditions, allowing for quicker and more efficient management. This review gathers and analyzes the results of various studies related to triage methods used in the Emergency Department (ED), their impact on wait times, and patient clinical outcomes. The findings suggest that standardized triage systems can significantly enhance workflow efficiency in the ED, reduce mortality, and improve patient satisfaction. A total of 1,440 articles were identified from various databases: 251 from PubMed, 1,090 from ScienceDirect, 83 from Google Scholar, 3 from Scopus, and 13 from ProQuest. After removing duplicates, 1,125 articles remained, title screening reduced this to 114 articles, followed by abstract screening which resulted in 31 articles. Finally, 13 articles were selected for full-text review. In conclusion, there is a need for the integration of evidence-based triage systems to review the importance of developing adaptive triage protocols to improve the effectiveness of emergency case management in the ED. However, challenges in implementation, such as adequate training and resource limitations, need to be addressed to achieve optimal outcomes.